Biochar as a Soil Amendment Tool: Effects on Soil Properties and Yield of Maize and Cabbage in Brong-Ahafo Region, Ghana - Akolgo, Gilbert Ayine; Kemausuor, Francis; Awafo, ,Edward Abingya (Open Journal of Soil Science, 2020)
Ghana’s soil is continuously declining in fertility due to continuous cultivation and rapid mineralization of its soil organic matter. Previous studies have touted the potential of biochar to help improve soil properties and increase the yield of crops. This study investigated the effects of the application of biochar on physicochemical properties of soil and the yield of maize and cabbage in Ghana. The study indicated that application of biochar significantly increased soil organic matter (SOM) from 3.88% (for control) to 5.72% (for biochar application rate 20 ton/ha and 0 ton/ha of NPK). It also increased soil pH from 6.55 in (for control) to 7.30 (for biochar application rate 20 ton/ha) and 0 ton/ha of nitrogen (N), phosphorus (P) and potassium (K) which can help ameliorate the soil acidity problem of Ghanaian soils. This field study, demonstrated that addition of biochar from sawdust increased the yield (between the control (0 ton/ha of biochar, 0% of recommended dose of NPK) and 20 ton/ha, 0% recommended dose of NPK) of maize and cabbage by 6.66% and 7.57% respectively. This study concluded that application of biochar offers a great potential to improve soil quality and the yield of maize and cabbage in Ghana
Keywords: Biochar; Physicochemical Properties; Soil Amendment; Ghana; Maize Yield; Power; University of Energy & Natural Resources; ACE: Energy and Environmental Sustainability